Profil Hemodinamik pada Soccer Pria Pra Lanjut Usia Selama Masa Latihan High Intensity Interval Training (HIIT) - Wilda Fauzia; Ana Khumaeroh; Andre Picessa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the hemodynamic profile of pre-elderly men during high intensity interval training (HIIT) soccer training (minisoccer). This research method used a quasy experimental design with one group pretest-posttest, the hemodynamic profile variables studied were heart rate, blood pressure and mean arterial pressure (MAP) as measured by a digital tensimeter and using the formula 1/3 systolic + 2/3 diastolic. The results of the study obtained were changes in heart rate, blood pressure and MAP before and after exercise and there were differences in the average hemodynamic profile between before and after exercise with a p value of 0.000 in heart rate, p value of 0.001 in systolic and p value of 0.006 in diastolic. as well as a p value of 0.003 at MAP. The conclusion of this study is that HIIT training can control heart rate, lower blood pressure and reduce minisoccer MAP and in general can improve heart health in adult men through a hemodynamic predictor profile. Keywords: HIIT Exercise, Pre-Elderly, Hemodynamic Profile